Activin receptor ligand traps in chronic kidney disease. Issue 5 (September 2018) - Jelkmann, Wolfgang
Abstract : Purpose of review: Sotatercept and luspatercept are recombinant soluble activin type-II receptor-IgG-Fc fusion proteins that are tested in clinical trials for the treatment of various types of anemias, including renal anemia. The mechanism of the action of the novel drugs is incompletely understood, but it seems to be based on the inactivation of soluble proteins of the transforming growth factor-ß (TGFß) family. This review considers pros and cons of the clinical use of the drugs in reference to the current therapy with recombinant erythropoiesis-stimulating agents (ESAs). Recent findings: One or more activin type-II receptor (ActRII) ligands appear to inhibit erythroid precursors, for example growth and differentiation factor 11. Trapping of these ligands by the recombinant ActRII fusion proteins, sotatercept and luspatercept increases red blood cell numbers and hemoglobin levels in humans. Reportedly, the novel compounds were well tolerated in trials on healthy volunteers and patients suffering from anemia due to chronic kidney disease or malignancies. On approval, the drugs may prove particularly useful in patients suffering from ineffective erythropoiesis, such as in myelodysplastic syndrome, multiple myeloma or ß-thalassemia, where ESAs are of little use. Independent of their effect on erythropoiesis, ActRII ligand traps were found to exert beneficial effects on renal tissue in experimental animals. Summary: ESAs are likely to remain standard of care in renal anemia. There is a need for a better understanding of the effects of ActRII ligand traps on TGFß-like proteins. The novel drugs have not been approved for sale as therapeutics so far. Their long-term efficacy and safety still needs to be proven, particularly with respect to immunogenicity. Antifibrotic effects may be worthy to be investigated in humans.